2017
DOI: 10.1186/s12883-017-0844-z
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource use and costs of multiple sclerosis patients in Germany before and during fampridine treatment

Abstract: BackgroundMultiple sclerosis (MS) patients often suffer from gait impairment and fampridine is indicated to medically improve walking ability in this population. Patient characteristics, healthcare resource use, and costs of MS patients on fampridine treatment for 12 months in Germany were analyzed.MethodsA retrospective claims database analysis was conducted including MS patients who initiated fampridine treatment (index date) between July 2011 and December 2013. Continuous insurance enrollment during 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…A recent study from Germany demonstrated that healthcare costs increases with severity but the inpatient costs decreases (31). Our study actually demonstrated the same but in different context.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A recent study from Germany demonstrated that healthcare costs increases with severity but the inpatient costs decreases (31). Our study actually demonstrated the same but in different context.…”
Section: Discussionsupporting
confidence: 78%
“…These costs are based on the exchange rates of the Central Bank of Iran, expressed in US dollars (a dollar equivalent to 42,000 IRR, on 30 May 2018) (31). The reference year was May 2017 to May 2018 for cost estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high prevalence of walking dysfunction in PwMS, the only approved medical treatment for improving MS-associated gait deficits is fampridine (4-aminopyridine, dalfampridine) [2]. Treatment with prolonged-release (PR)-fampridine results in significant and persisting improvements in ambulatory function in a proportion of PwMS [3][4][5][6][7][8][9] by blocking potassium channels of demyelinated axons [10].…”
Section: Introductionmentioning
confidence: 99%
“…The multivariate linear regression was used for assigning the relationship between the disease condition and various costs imposed on pwms. These costs are based on the exchange rates of the Central Bank of Iran, expressed in US dollars and EURO (a USD and EURO equivalent to 42,000 IRR and 49,280 IRR on 20 May 2018, respectively) [34]. Due to sanction, we could not provide international Dollar for 2018.…”
Section: Discussionmentioning
confidence: 99%